2006
DOI: 10.1016/j.otohns.2005.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Coblation Adenotonsillectomy: An Improvement Over Electrocautery Technique?

Abstract: B-3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 13 publications
1
41
2
1
Order By: Relevance
“…These data appear different from our own experience and that of the posttonsillectomy hemorrhage literature [42,43,44,45,46,47,48,49,50]. In their study involving the use of dexamethasone for emesis prophylaxis in adenotonsillectomy, Gunter et al [51] found only 1 out of 230 subjects (0.4%) experienced hemorrhage in the first 24 h following surgery[.…”
Section: A Controversy Emerges: the Trial Of Czarnetzki Et Alcontrasting
confidence: 71%
“…These data appear different from our own experience and that of the posttonsillectomy hemorrhage literature [42,43,44,45,46,47,48,49,50]. In their study involving the use of dexamethasone for emesis prophylaxis in adenotonsillectomy, Gunter et al [51] found only 1 out of 230 subjects (0.4%) experienced hemorrhage in the first 24 h following surgery[.…”
Section: A Controversy Emerges: the Trial Of Czarnetzki Et Alcontrasting
confidence: 71%
“…A specific concern for children under 3 years of age was raised by the retrospective study by Glade et al [ 12 ; level 3]. A higher bleeding rate was seen in the 104 children who had Coblation compared to the 187 who had MES (p = 0.0065) [12] .…”
Section: Secondary Hemorrhagementioning
confidence: 99%
“…Coblation adenoidectomy caused less postoperative neck pain than curette/cautery adenoidectomy without significant advantage over cautery adenoidectomy [18] . Children who received Coblation electrosurgery tonsillectomy appeared to experience a better quality postoperative course, with no detriment to operative benefits of conventional electrosurgery.…”
Section: Discussionmentioning
confidence: 86%